2016
DOI: 10.1007/s00402-016-2465-1
|View full text |Cite
|
Sign up to set email alerts
|

Open wedge high tibial osteotomy (HTO) versus mobile bearing unicondylar medial joint replacement: five years results

Abstract: The results of this study showed that 5 years after surgery patients after UKA had less residual pain and symptoms than patients after UKA. These advantages might result in a higher quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 25 publications
3
34
1
1
Order By: Relevance
“…Generally, more complication were noted after a valgus HTO with significant difference found between the two groups ( p  < 0.001; OR = 3.08; 95% CI = 1.76, 5.39), reflecting results from seven studies [8, 9, 12, 15, 17, 19, 20] with 559 patients.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…Generally, more complication were noted after a valgus HTO with significant difference found between the two groups ( p  < 0.001; OR = 3.08; 95% CI = 1.76, 5.39), reflecting results from seven studies [8, 9, 12, 15, 17, 19, 20] with 559 patients.…”
Section: Resultsmentioning
confidence: 71%
“…The inclusion criteria for the other studies were varied or unclear. Six papers [5, 12, 13, 15, 18, 20] reported the cohorts using the Ahlbäck OA score, and three papers [9, 17, 21] used the Kellgreen–Lawrence (K/L) score. All of the included studies described the type of procedure, except one [18] in the HTO group and three [8, 16, 18] in the UKA group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the two procedures were reliable and effective for medial osteoarthritis of the knee and had similar reoperation rates; however, clinical outcomes of UKA was superior to those of HTO. Recently, Petersen and Metzlaff24) compared minimum 5 year follow-up results of the frequently used opening wedge HTO and mobile-bearing UKA performed in patients between 55 and 65 years of age. There was no significant difference in terms of reoperation rates; however, the incidence of residual pain and symptoms was higher after HTO, which they suggested patients should be informed of prior to surgery.…”
Section: Discussionmentioning
confidence: 99%